168 Calf-inated Cups: Disposable coffee cups as a fiber source in ruminant diets. (29th July 2019) - Wood, Shelby L; Baker, Lauren M; Cherry, Nichole M; Muir, James P; Smith, William B
Abstract: Per unit energy, fiber is among the most expensive components of the ruminant diet. Wastes from human enterprises may represent the next step in feedstuff investigation. In an effort to minimize the anthropogenic waste contribution, and as a means to find a more cost-efficient resource to feed ruminant animals, our objective was to determine the nutritive value of disposable coffee cups and warmer sleeves in relation to ruminant nutrition. Discarded cups and warmer sleeves were collected from employees at Tarleton State University in fall of 2017. Cups were obtained from five sources, and warmer sleeves were obtained from two sources. Cups and sleeves were dried at 55°C for 72 h and ground to pass through a 2-mm screen. Ground samples were subjected to a batch-culture in vitro true digestibility (IVTD) assay. Original samples and incubated residues were then assayed for DM, NDF, ADF, and CP. Data were analyzed as a random effects model completely randomized design using the MIXED procedure of SAS. There was no effect (P > 0.05) of source (n = 5) or type (cup or sleeve) for contribution to variance of NDF, ADF, IVTD, and in vitro NDF digestibility (IVNDFD). Mean values for NDF, ADF, IVTD, and IVNDFD across samples were 89.5, 81.4, 24.5, and 18.7%, respectively. Results indicate a low digestibility coefficient for these waste products, thus meaning its use as a feedstuff could be questionable. However, such results provide insight into niches where this product and other anthropogenic wastes may fit in the larger picture of ruminant nutrition